Biological and Physical-Chemical Properties of Yersinia pseudotuberculosis Cultures in the Process of Submerged Cultivation at Various Temperatures - K. E. Gavrilov; E. V. Serebryakova; T. Yu. Dunyasheva; N. N. Zaytseva; Yu. D. Eremenko; V. S. Lobastov; A. A. Byvalov; S. L. Kuznetsov; I. V. Borisevich (Проблемы особо опасных инфекций, 2010)
Biological and physical-chemical properties of the pseudotuberculosis agent cultures were shown to be diverse in the process of submerged cultivation at various temperatures. The microbe cultivation at the increased temperature (37°C) was characterized by fast development and death of the population. Decelerated lag phase and extended exponential phase were observed under the conditions of cultivation at low temperature. The culture grown at 27 °C was found to get an intermediate position between those grown at 10 and 37 °C.